2014
DOI: 10.1007/s11605-013-2404-1
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Magnetic Resonance Enterography in Predicting Findings and Optimizing Surgical Approach in Crohn's Disease

Abstract: Surgical strategy and approach are correctly predicted by magnetic resonance enterography in the majority of patients with complicated Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 18 publications
4
11
0
1
Order By: Relevance
“…The accuracy of MRE in detecting stenoses in our study was also consistent with the results reported by the Italian group [11] .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The accuracy of MRE in detecting stenoses in our study was also consistent with the results reported by the Italian group [11] .…”
Section: Discussionsupporting
confidence: 93%
“…In our study, MRE had lower specificity in detecting stenoses than abscesses or fistulas, a finding similar to that previously reported by Spinelli et al [11] . The accuracy of MRE in detecting stenoses in our study was also consistent with the results reported by the Italian group [11] .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…1 The independent blind reporting provides strength to the study. We have several points for the author's consideration.…”
mentioning
confidence: 99%